Effects of black pepper and turmeric powder on growth performance, gut health, meat quality, and fatty acid profile of Japanese quail - Ashayerizadeh, O.; Dastar, B.; Shams Shargh, M.; A. Soumeh, E.; Jazi, V. (Frontiers in Physiology, 2023)
In poultry production, the search for alternatives to in-feed antibiotics continues unabated. This study investigated the effects of dietary supplementation of black pepper and turmeric powder, separately or in combination, on the growth performance, gastrointestinal microbial population, intestinal morphology, serum biochemical parameters, meat quality, and meat fatty acid profile in Japanese quails. Five hundred-day-old mixed-sex Japanese quail chicks were randomly assigned to one of five treatments: a control diet (CON); CON + 0.2% antibiotic flavomycin as an antibiotic growth promoter (AGP); CON + 0.5% turmeric powder (TUP); CON + 0.5% black pepper powder (BPP); and CON + 0.5% TUP and 0.5% BPP (MIX). The findings showed that quail chicks fed AGP and TUP throughout the rearing period had better body weight gain (P = 0.007) and feed conversion ratio (P = 0.02) than the other treatments. The TUP, BPP, and MIX feeds reduced (P = 0.005) abdominal fat percentage. The MIX group had a better breast muscle water-holding capacity (P = 0.04) and lightness index (P = 0.02) and lower (P = 0.02) malondialdehyde concentration after seven days of refrigerated storage. Feeding BPP, TUP, and MIX diets decreased (P = 0.001) serum cholesterol concentration. Quail chicks fed the CON diet showed significantly higher coliform counts in the crop and ileum (P < 0.001), whereas the lactic acid bacterial population was lower (P = 0.008) in the ileum. Birds that received the MIX diet exhibited a higher (P = 0.02) villus height to crypt depth ratio in the duodenum compared to the other groups. The tested feed additives increased (P < 0.001) villus height in the jejunum and ileum compared to other groups. Feeding the TUP, BPP, and MIX diets reduced (P < 0.001) total saturated fatty acid content and increased (P = 0.004) total polyunsaturated fatty acid concentration, where the MIX diet had the best results. Overall, the present data indicate that supplementing the basal diet with turmeric powder enhances the growth performance of Japanese quails. In some respects, such as gut health and meat quality, combining turmeric powder and black pepper powder was more effective than using them independently.